“Clear Eyes, Full Hearts, Can’t Lose”: Friday Night Lights and Victorian Fictions of Provincial Life - King, Amy (Romanticism and Victorianism on the Net, 2013)
Friday Night Lights, the 2006-2011 television series about a Texas high school football team, owes a debt to readers of Victorian fictions of everyday life and provincial fiction. Habituated to the quotidian, readers of Victorian fictions of provincial life are arguably the best equipped for understanding the critically-acclaimed television series, for in it, like the fiction that precedes it, hardly anything of moment happens. Plot and telos are hardly the point; the series locates its energies in the stuff of everyday life rather than in the logic of suspense. Recent work on the provincial novel helps us understand the politics of FNL in a way that goes beyond its own explicit themes of race, class mobility, and education. That both the Democratic and Republican candidates for the U.S. presidency in 2012 used the fictional team’s mantra—“Clear Eyes, Full Heart, Can’t Lose”—suggests the extent to which the ideas of the show tapped into a politics about nation. Paradoxically, the show’s deliberately provincial scope allowed it symbolically to unify the nation.